2015
DOI: 10.3390/jintelligence3030091
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects between Openness and Fluid Intelligence Predicting Scholastic Performance

Abstract: Abstract:Figural reasoning as an indicator of fluid intelligence and the domains of the Five Factor Model were explored as predictors of scholastic performance. A total of 836 Chinese secondary school students (406 girls) from grades 7 to 11 participated. Figural reasoning, as measured by Raven's Standard Progressive Matrices, predicted performance in Math, Chinese, and English, and also for a composite score. Among the personality domains, Openness had a positive effect on performance for all subjects after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 76 publications
(124 reference statements)
0
34
1
Order By: Relevance
“…Studies that examined Conscientiousness as a moderator of GMA for predicting job performance reveal inconsistent findings: Some studies found no support for an interaction (Mount, Barrick, & Strauss, 1999;Sackett, Gruys, & Ellingson, 1998), whereas other studies revealed support for interaction effects between GMA and achievement motivation related facets of Conscientiousness (Perry, Hunter, Witt, & Harris, 2010), and between GMA and contextualized measures of achievement motivation (Hirschfeld, Lawson, & Mossholder, 2004). In educational psychology, the effect of GMA on grade point average was found to be stronger at higher levels of (the facets of) Conscientiousness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Ziegler, Knogler, & Bühner, 2009; but see Zhang & Ziegler, 2015). Openness has also been found to moderate the effect of GMA on academic performance, such that the effect of GMA on academic performance is stronger at lower levels of Openness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Zhang & Ziegler, 2015).…”
Section: Interaction Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that examined Conscientiousness as a moderator of GMA for predicting job performance reveal inconsistent findings: Some studies found no support for an interaction (Mount, Barrick, & Strauss, 1999;Sackett, Gruys, & Ellingson, 1998), whereas other studies revealed support for interaction effects between GMA and achievement motivation related facets of Conscientiousness (Perry, Hunter, Witt, & Harris, 2010), and between GMA and contextualized measures of achievement motivation (Hirschfeld, Lawson, & Mossholder, 2004). In educational psychology, the effect of GMA on grade point average was found to be stronger at higher levels of (the facets of) Conscientiousness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Ziegler, Knogler, & Bühner, 2009; but see Zhang & Ziegler, 2015). Openness has also been found to moderate the effect of GMA on academic performance, such that the effect of GMA on academic performance is stronger at lower levels of Openness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Zhang & Ziegler, 2015).…”
Section: Interaction Effectsmentioning
confidence: 99%
“…In educational psychology, the effect of GMA on grade point average was found to be stronger at higher levels of (the facets of) Conscientiousness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Ziegler, Knogler, & Bühner, 2009; but see Zhang & Ziegler, 2015). Openness has also been found to moderate the effect of GMA on academic performance, such that the effect of GMA on academic performance is stronger at lower levels of Openness (Bergold & Steinmayr, 2018;Di Domenico & Fournier, 2015;Zhang & Ziegler, 2015). GMA and Openness have a compensatory effect on performance, and hence, the lower one's level of Openness, the larger is the relative contribution of GMA on performance (see Ziegler, Danay, Heene, Asendorpf, & Bühner, 2012).…”
Section: Interaction Effectsmentioning
confidence: 99%
“…Another understanding of innovation capability based on the knowledge creation process was proposed by Zhang et al [13]. They suggested that firms should first be aware of the internal and external changes-correctly interpreting the effect of dynamic information on firm performance-and then take actions in effective response to the changes and keep dynamic adaptability between the firm itself and the environment.…”
Section: Innovation Capabilitymentioning
confidence: 99%
“…This study employed [13] an understanding of a firm's innovation capability to analyze how the capability influences the choices of firms' innovation types. A firm's innovation capability was measured by four aspects: awareness, interpretation, decision making, and implementation.…”
Section: Innovation Capabilitymentioning
confidence: 99%
See 1 more Smart Citation